Influence of psychosocial factors on student academic performance in a college in Yobe State, Nigeria - Kolo, Garba Ali (2017)
Poor student academic performance in institution of learning in Nigeria has become a serious challenge to both the parents and government because in Nigeria, academic performance is considered as a criterion for one’s personal progress and societal development in general and is affected by many psychosocial factors either positively or negatively in educational institutions. The main objective of this study was to examine the influence of psychosocial factors (perception of student towards lecturer attitude, academic self-efficacy and student-lecturer interaction) on students’ academic performance in Federal College of Education (Technical) Potiskum, Yobe State, Nigeria. A quantitative research approach was used. A total samples of 339 final year students (245 Males and 94 Females) between the ages of 19 to 34 years old were collected. The data collection exercise was done by the means of self-administered questionnaire and then analyzed with SPSS Software version 22. Descriptive statistics, Pearson’s correlational as well as multiple regression by stepwise method were employed in this study. The findings indicated that, there were positive and significant relationship between perception of students’ towards lecturers attitudes and academic performance (r=.464, p< 0.01). Also, positive and significant relationship between academic self-efficacy and academic performance (r=.342, p< 0.01). Furthermore, the results showed that, there was positive and significant relationship between studentslecturers interaction and academic performance (r=.407, p< 0.01). The findings revealed that, the independent variables; i.e. psychosocial factors (attitude and interaction), explained 65.6% of variation for dependent variable (academic performance) and based on the standardized regression weight the independent variable of perception of students towards lecturers attitude, with highest standardized regression weight (β= 0.786) among other independent variables emerged as the strongest predictor of academic performance among the respondents. The results of present study can contributes to the body of knowledge and has remarkable implications for academicians and policy makers on how to enhance students’ academic performance in Colleges of education in Nigeria. Therefore, it is recommended that, Nigerian Federal Ministry of Education should be organizing a workshops and seminars to College managements and academic staff on importance of demonstrating positive attitudes to their students which is considered as vital on effective teaching and learning in academic environment as evident in present study with the view to improve students’ academic performance positively. The findings also recommended that, future research on other psychosocial factors like stress, culture, socio-economic status, motivation and religion should be given priority.